Enhanced thermal stability of piezoelectricity in lead-free (Ba, Ca)(Ti, Zr)O3 systems through tailoring phase transition behavior. Issue 8 (1st June 2019) - Yin, Mengye; Zhou, Chao; Ren, Shuai; Hao, Yanshuang; Fang, Minxia; Wang, Wenjia; Gao, Jinghui; Ma, Tianyu; Zhang, Lixue; Yang, Sen; Ren, Xiaobing
Abstract: Good thermal stability in lead-free BaTiO3 ceramics is important for their applications above room temperature. In this study, thermal stable piezoelectricity in lead-free (Ba, Ca)(Ti, Zr)O3 ceramics was enhanced by tailoring their phase transition behaviors. Comparison between (1- x )Ba(Ti0.8 Zr0.2 )O3 - x (Ba0.65 Ca0.35 )TiO3 and (1- y )Ba(Ti0.8 Zr0.2 )O3 - y (Ba0.95 Ca0.05 )TiO3 revealed that latter system at y  = 0.80 had much better thermal stable piezoelectric coefficient than the former at x  = 0.45. Both systems crystalized in tetragonal to orthorhombic phase boundary at room temperature. The phase transition temperature and degree of diffusion were adjusted by Ca and Zr ions contents and demonstrated great influence on temperature dependent dielectric permittivity, hysteresis loops, and in-situ domain structures. The improved thermal stability of (1- y )Ba(Ti0.8 Zr0.2 )O3 - y (Ba0.95 Ca0.05 )TiO3 prepared at y  = 0.80 was linked to its higher paraelectric to ferroelectric phase transition temperature ( T m  = 115.7 °C) and less degree of diffusion (degree of diffusion constant γ  = 1.35). By comparison, (1- x )Ba(Ti0.8 Zr0.2 )O3 - x (Ba0.65 Ca0.35 )TiO3 prepared at x  = 0.45 revealed T m  = 81.3 °C and γ  = 1.65. Overall, these findings look promising for future stimulation of phase transition behaviors and design of piezoelectric materials with good thermal stabilities.